Effect of in ovo injection of glucose on egg hatchability, chick hatch-weight, productivity and carcass characteristics of indigenous Potchefstroom Koekoek chickens - Letsoalo, Tshegofatso Maapeya Caroline (University of Limpopo, 2016)
Three experiments were conducted to determine the effect of in ovo glucose injection on egg hatchability, chick hatch-weight, productivity and carcass characteristics of indigenous Potchefstroom koekoek chickens. A complete randomized design was used in all the three parts of the study (from incubation, 1-49 days old unsexed chickens and 50-91 days old female chickens). On day 18 of incubation the developing eggs were subjected to the following treatments: 0- (no glucose or water injected), 0+ (only water injected), 5, 10, 15 or 20 mg of glucose per egg. Each treatment had three replications and there were 20 eggs per replicate. A quadratic model was used to determine in ovo glucose injection levels for optimal egg hatchability, chick hatch-weight and chick to egg weight ratio of Potchefstroom koekoek chickens. In ovo glucose injection improved (P<0.05) egg hatchability, chick hatch-weight and chick to egg weight ratio of the chickens. Egg hatchability, chick hatch-weight and chick to egg weight ratio Potchefstroom koekoek chickens were optimized at different injection levels of 4.50, 10.43 and 12.00 mg of glucose per egg, respectively. Unsexed day-old chicks from the first experiment (according to their initial treatments and replicates) were used in a complete randomized design having six treatments, replicated three times, and having ten birds per replicate. Glucose injection levels increased (P<0.05) feed intake, growth rate, feed conversion ratio, live weight, metabolisable energy and nitrogen retention of female Potchefstroom koekoek chickens aged 1 to 49 days. However, growth rate, live weight, metabolisable energy intake and nitrogen retention of the chickens were optimized at glucose injection levels of 3.92, 4.36, 10.67 and 13.50 mg per egg, respectively. Female chickens from the second part of the study (according to their initial treatments and replicates) were used in a complete randomized design having six treatments, replicated three times, and having five birds per replicate. In ovo glucose injection levels improved (P<0.05) on feed intake, growth rate, feed conversion ratio, live weight, metabolisable energy and nitrogen retention of female Potchefstroom koekoek chickens aged 50 to 91 days. However, only feed conversion ratio and metabolisable energy intake of the chickens were optimized at glucose injection levels of 12.15 and 5.57 mg per egg, respectively. Injection level also improved (P<0.05) carcass, breast, v drumstick, thigh, wing, gizzard and liver weights of female Potchefstroom koekoek chickens aged 13 weeks. In ovo glucose injection increased (P<0.05) breast meat tenderness, juiciness and flavour of female Potchefstroom koekoek chickens aged 91 days. However, breast tenderness, juiciness and flavour of female Potchefstroom koekoek chickens were optimized injection levels of 13.50, 19.25 and 10.83 mg of glucose per egg, respectively. No chicken deaths were observe
Thesis (MSc. Agriculture (Animal Production)) -- University of Limpopo, 2015
Keywords: Ovo glucose infection; Egg hatchability; Chicken hatch weight productivity; Indigenous chickens; Eggs -- Hatchability; Chickens -- Embryos